Ménétrier’s disease and severe gastric ulcers associated with cytomegalovirus infection in an immunocompetent child: a case report - Canan, Oğuz; Özçay, Figen; Bilezikçi, Banu (The Turkish Journal of Pediatrics, 2008)
In pediatric patients, Ménétrier’s disease is an uncommon clinical entity that has been rarely described only as sporadic cases, and the etiology is unclear. These patients usually have a self-limiting clinical course. Cytomegalovirus is an important pathogen in the immunocompromised host. However, cytomegalovirus infection can be detected in non-immunocompromised children. We discuss the possible role of cytomegalovirus infection in both Menetrier’s disease and severe gastric ulcers in an immunocompetent child.